Inclusive Service Management for Students with Disabilities: A Social Capital Perspective of Pierre Bourdieu - Qomariah, Zaitun; Masdar Hilmy; Desi Erawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the role of social capital in disability service management in higher education using Pierre Bourdieu’s theoretical framework. Inclusive services for students with disabilities continue to face challenges, such as inadequate infrastructure, rigid curricula, and limited support from academic staff. Employing a qualitative approach through a literature review of ten relevant studies, this research reveals that social capital, through relational networks, peer support, and institutional policies, plays a crucial role in enhancing access to resources, academic assistance, and social integration for students with disabilities. The findings also show that social, cultural, and symbolic capital interaction can strengthen or weaken inclusive service practices. This study contributes theoretically by contextualizing social capital theory within inclusive higher education. It offers strategic recommendations for universities to improve policy frameworks, develop supportive infrastructure, and optimize social support systems for students with disabilities.